An Analysis of Logical Fallacy in Argument of Campaign Team of Joko Widodo and Prabowo Subianto - Rahmaddin Daeli (Universitas Negeri Padang, 2020)
This research was aimed to find the types of logical fallacies in argument of campaign team debate of Joko Widodo and Prabowo Subianto. This research was descriptive qualitative. The data were analyzed by using theory of Damer (2009). The result of the research showed that of all sixty types of fallacy, there were only fifteen types were found. There are twelve types of fallacies produced by campaign team of Joko Widodo with twenty six occurrences and nine types of fallacies produced by campaign team of Prabowo with thirty three occurrences. Drawing the wrong conclusion fallacy was the most dominant type produced by campaign team of Jokowi with the proportion 19.23 %. The most dominant types produced by campaign team of Prabowo are using the wrong reasons and contrary-to-fact-hypothesis with the proportion 33.33%.Key words: Logical fallacy, argument, campaign team debate